(untitled) (New Delhi, 2006)
This book disscusses puioneering methods and applications, which precipitate the solution of complex problem. Since visuallization has become an important scientific tool, especially in the analysis of complex situations, it is treated in close connectio with other areas covered in this book
Keywords: Computer algorithms.,Numerical analysis.,Mathematical models,Mathematics,Giải thuật máy tính,Giải tích số,Mô hình toán,Toán; Data processing,Xử lý dữ liệu